INNOVATIVE APPROACHES IN EDUCATION (Multidisciplinary Journal of Science and Technology, 2024)
Along with the creation of an innovative environment in the educational system, the issues of innovative production of educational processes, development of innovative education, trends and prospects, implementation of innovative activities in the development of innovative education are discussed.